2008
DOI: 10.1676/06-156.1
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Success of House Wrens in Suburban and Rural Landscapes

Abstract: We investigated the impacts of urbanization on reproductive success of House Wrens (Troglodytes aedon). We compared reproductive effort and success for 33 nesting attempts in suburban sites (2.5-10 buildings/ha) and 43 nesting attempts in rural sites (Ͻ2.5 buildings/ha) in and around the Washington, D.C.-Baltimore, Maryland, metropolitan area. There were no differences in clutch initiation dates or clutch sizes between suburban and rural nests. However, nestlings at suburban nests weighed less and had smaller … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 28 publications
2
32
1
Order By: Relevance
“…However, we did not find evidence that differences in laying dates or breeding performance between types of nests could be attributed to younger or better-quality pairs being attracted to any type of nest box. Other studies that have reported higher breeding success of birds in humanized areas have interpreted such results as a consequence of increased food abundance or reduced predation pressure [4346]. These effects may have played a role in creating differences between disturbed and quiet nests in our study as well.…”
Section: Discussionsupporting
confidence: 48%
“…However, we did not find evidence that differences in laying dates or breeding performance between types of nests could be attributed to younger or better-quality pairs being attracted to any type of nest box. Other studies that have reported higher breeding success of birds in humanized areas have interpreted such results as a consequence of increased food abundance or reduced predation pressure [4346]. These effects may have played a role in creating differences between disturbed and quiet nests in our study as well.…”
Section: Discussionsupporting
confidence: 48%
“…Although cities generally have greater numbers of generalist and opportunistic predators that prey upon bird nests (Sorace 2002;Prange and Geh-rt 2004;Fischer et al 2012), there is paradox in that links between urbanization and nest predation are surprisingly weak with mixed empirical support (Chamberlain et al 2009;Fischer et al 2012). Rural nest survival has been similar (Reidy et al 2009;Burhans and Thompson 2006;Rodewald et al 2013), greater (Newhouse et al 2008;Ryder et al 2010;Stracey and Robinson 2012), and Table 8.1 Cause-specific mortality for terrestrial vertebrates derived from radiotelemetry. Number of mortalities ( n) and the percentage of mortalities by three types of mortality.…”
Section: Predationmentioning
confidence: 99%
“…In their review of the avian literature, Chamberlain et al (2009) reported that annual productivity was greater in urban than nonurban habitats for seven of eight urban adapting species though nestling weight was lower in urban than rural areas for nine of ten urban adapters. Brood size of northern goshawks ( Accipeter gentilis; Solonen and Ursin 2008) as well as number of young fledged by northern mockingbirds (Stracey and Robinson 2012) and house wrens ( Troglodytes aedon; Newhouse et al 2008) was greater in urban than rural sites. Urban adapting mammalian species that are able to exploit anthropogenic resources also tend to have elevated reproductive rates compared to rural populations.…”
Section: Reproductive Outputmentioning
confidence: 99%
“…Unfortunately, urban environments also contain a host of negative factors that could impair total productivity. For example, birds in urban environments may face reduced post-fledging survival (A. Balogh and P. P. Marra, unpublished manuscript; but see Whittaker and Marzluff 2009), increased nest parasitism, fewer breeding attempts and fledged young (Rodewald and Shustack 2008), or reduced physical condition of young (Newhouse et al 2008). Moreover, species living within the urban/ suburban matrix are also subject to an array of other factors that could negatively affect various aspects of their life histories including increased noise pollution (Slabbekorn and Peet 2003), exposure to contaminants (Roux and Marra 2007), and exposure to novel predation pressures (e.g., cats; Baker et al 2005).…”
Section: Figmentioning
confidence: 99%